2016
DOI: 10.1016/bs.irn.2016.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Marijuana Use on Brain Structure and Function

Abstract: Marijuana, behind only tobacco and alcohol, is the most popular recreational drug in America with prevalence rates of use rising over the past decade. A wide range of research has highlighted neurocognitive deficits associated with marijuana use, particularly when initiated during childhood or adolescence. Neuroimaging, describing alterations to brain structure and function, has begun to provide a picture of possible mechanisms associated with the deleterious effects of marijuana use. This chapter provides a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 124 publications
2
6
0
Order By: Relevance
“…In response to interference compared to neutral trials, marijuana users had larger increases in activation in the right and left supramarginal gyrus, with the left cluster extending into the posterior MTG. These findings are consistent with prior studies on the effects of chronic marijuana use, which generally report alterations in frontal, parietal, and temporal regions during cognitive tasks (Batalla et al, 2013; Brumback et al, 2016; Martin-Santos et al, 2010). Such hyperactivity may serve as a mechanism to compensate for decreased efficiency and neural capacity due to marijuana use (Brumback et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In response to interference compared to neutral trials, marijuana users had larger increases in activation in the right and left supramarginal gyrus, with the left cluster extending into the posterior MTG. These findings are consistent with prior studies on the effects of chronic marijuana use, which generally report alterations in frontal, parietal, and temporal regions during cognitive tasks (Batalla et al, 2013; Brumback et al, 2016; Martin-Santos et al, 2010). Such hyperactivity may serve as a mechanism to compensate for decreased efficiency and neural capacity due to marijuana use (Brumback et al, 2016).…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with prior studies on the effects of chronic marijuana use, which generally report alterations in frontal, parietal, and temporal regions during cognitive tasks (Batalla et al, 2013; Brumback et al, 2016; Martin-Santos et al, 2010). Such hyperactivity may serve as a mechanism to compensate for decreased efficiency and neural capacity due to marijuana use (Brumback et al, 2016). Compensatory theories posit that, in order to preserve cognitive function, additional regions that are not typically activated for a specific task must be engaged to maintain performance (Barulli and Stern, 2013).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous work has reviewed both the cognitive [5,7,[51][52][53][54] and neurofunctional [55][56][57][58] effects of cannabis, both acutely and chronically, in the context of memory processing. Although a number of systematic reviews have summarised brain-structural alterations [56,59,60] as well brain-functional alterations [56,[59][60][61][62][63] more broadly over a wide range of cognitive domains associated with cannabis use, functional alterations in the context of memory processing in cannabis users have not been systematically and comprehensively summarized to include up-to-date literature [54]. Therefore, in order to summarise the current literature, we have conducted a systematic review of studies that have employed functional magnetic resonance (fMRI) techniques in conjunction with cognitive activation paradigms that involve memory processing, to investigate memory-related brain-functional alterations in long-term cannabis users (CU) compared to nonusers (NU).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to changes on cognitive testing, studies employing brain imaging techniques have revealed structural changes associated with prolonged cannabis use and with initiation of use in youth. A recent review of this literature [117] demonstrated that consistent evidence exists for alterations in the medial temporal, frontal and cerebellar brain regions. Structural changes in both gray matter and white matter have been reported on functional MRI (fMRI) imaging.…”
Section: Cannabis Use In Youthmentioning
confidence: 99%